Structural and electrical characterization of multilayer Al2O3/ZnO nanolaminates grown by atomic layer deposition. (15th November 2017) - Martínez-Castelo, J.R.; López, J.; Domínguez, D.; Murillo, E.; Machorro, R.; Borbón-Nuñez, H.A.; Fernandez-Alvarez, I.; Arias, A.; Curiel, M.; Nedev, N.; Farías, M.H.; Tiznado, H.
Abstract: Nanolaminates formed by several bilayers of Al2 O3 and ZnO (AZA), grown by atomic layer deposition from Trimethyl aluminum, Diethyl zinc and water as co-reactants, were deposited on n-type (100) silicon substrates. A set of 5 nanolaminates with a total thickness of about 100 nm, containing several Al2 O3 /ZnO bilayers with thicknesses of 0.28, 0.38, 2, 10 and 20 nm, were prepared. XRD shows an evolution from amorphous to crystalline structure as a function of bilayer thickness. Capacitance-Voltage (C-V) and Current-Voltage (I-V) electrical characterization was carried out in order to evaluate the potential of the nanolaminates for microelectronic applications. Dielectric constant values between 8.3 and 9.6 were obtained, depending on bilayer thickness. The MOS capacitors exhibited net equivalent oxide thickness values between 44 and 38 nm.